The Degree of Application of School Principals’ Management by Objectives and Its Impact on Self-Efficacy of Teachers from Their Point of View - An Empirical Study on the public schools in Amman- - Abu Hamda, Obai Talal (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of application of school principals’ management by objectives in public schools in the capital, Amman, and its impact on self-efficacy of teachers from their point of view. The questionnaire was used as a tool to collect data, Correlative approach was used. The study sample consisted of (394) of teachers in the Kasbah of Amman. The results of the study showed that the degree of application of school principals’ management by objectives in government schools in the capital, Amman from teachers’ point of view was high. Furthermore, the degree of self-efficacy of teachers in public schools in the capital Amman from their point of view was moderate. The study recommended that the school principal should develop a plan for the objectives and identify the different strategies and modern methods that help in achieving these goals.